The association of enchondromatosis with malignant transformed chondrosarcoma and ovarian juvenile granulosa cell tumor (Ollier disease) - Andrea Burgetova; Zdenek Matejovsky; Michal Zikan; Jiri Slama; Pavel Dundr; Petr Skapa; Kamila Benkova; David Cibula; Daniela Fischerova (Elsevier, 2017)
Objective: Ovarian juvenile granulosa cell tumor has an interesting association with multiple enchondromatosis (Ollier disease and Maffucci syndrome) and should be considered a leading diagnosis when an ovarian mass is found in young patients with these conditions. Besides the association with nonskeletal malignancies, there is a high risk of malignant transformation of enchondroma in chondrosarcoma as was also the case in this instance. Case Report: The report uses multiple images to document the representative and characteristic markers of multiple enchondromas in a 22-year-old patient with Ollier disease complicated by malignant transformation of chondrosarcoma and in whom the disease is associated with ovarian juvenile granulosa cell tumor of the right ovary. Conclusion: It is important to recognize that when the female patient presents with enchondromatosis and a large unilateral multilocular-solid ovarian mass, the specific diagnosis of granulosa cell tumor can be made with high accuracy.